Thị trường và đô la Mỹ trong cơ chế kinh tế mới - Lê, Xuân Nghĩa (2011)
Tác giả: Lê Xuân Nghĩa, PTS; Lê Quốc Huy; Vũ Xuân Đào; Nguyễn Cao Siêu; Đỗ Xuân Trường; Phạm Ngọc Phong; Phạm Xuân Hà; Nguyễn Công Nghiệp; Nguyễn Văn Sơn; Đoàn Văn Trường -- Từ khóa: Vàng; Đô la Mỹ; Thị trường; Kinh tế thị trường